The Effect of Digital Marketing on Purchase Loyalty with Customer Satisfaction as an Intervening Variable on Products Starbucks in Sukoharjo - Bangkit Adjie Santoso; Wuryaningsih Dwi Lestari (IAIN Palopo, 2023)
The purpose of this study was to determine the effect of digital marketing on purchase loyalty with customer satisfaction as an intervening variable on Starbucks products in Sukoharjo. This research method is quantitative. The population in this study was Starbuck Coffee consumers in Sukoharjo. The sampling technique for this research is nonprobability sampling. The sample in this study amounted to 100 respondents. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The results of this study are digital marketing has a significant positive effect on purchase loyalty. Digital marketing has a significant positive effect on customer satisfaction. Customer satisfaction has a significant positive effect on digital marketing. The conclusion of this study is that digital marketing affects purchase loyalty with customer satisfaction as an intervening variable on Starbucks products in Sukoharjo